An ad-hoc unicursal protocol for stable and long-lived communication systems in disaster situations. (19th July 2010) - Asakura, Koichi; Takikawa, Hiroya; Oishi, Junya; Watanabe, Toyohide
In this paper, we propose an ad-hoc unicursal protocol for communication systems in disaster situations. This protocol is designed for gathering information about rescues effectively in a big earthquake. For the longevity of networks, terminals are connected to each other in linear form in our protocol, which makes the communication loads among terminals relatively equal. In order to decrease frequency of packet sending, our protocol introduces virtual terminals, in which two neighbouring terminals activate alternatively. Experimental results show that our protocol needs less packets and that the average life time of terminals is longer than other protocols.